Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper reviews public expenditure in Lithuania with a view to identify areas for which deeper reforms may be warranted to improve spending efficiency and contain future spending pressures. The paper benchmarks spending levels and spending composition in Lithuania against those in other European countries. The 31 European countries covered in the benchmarking exercise include the EU-28 plus Iceland, Norway, and Switzerland. Reflecting the tendency for public spending to increase with income, Lithuania's spending as a share of GDP is compared with the European Union average spending controlling for GDP per capita. The paper also tries to assess spending relative to outcomes to get a sense of spending efficiency.